The Effectiveness of Content-Based Marketing Campaigns in Attracting Gen Z Consumers - Danis Maulana; Devi Yuliantina; Ristanti Akseptori; Andriya Risdwiyanto (PT. Hafasy Dwi Nawasena, 2025)
Generation Z grew up in a digital era dominated by technology and social media, thus affecting their consumption patterns and preferences for marketing content. Studies show that they trust recommendations from influencers and organic content more than conventional advertising. With shorter attention spans, effective marketing content should be concise, engaging, and easy to understand. Platforms such as TikTok, Instagram Reels, and YouTube Shorts are the main tools in reaching this young audience. However, the main challenge is creating content that not only grabs momentary attention but also builds long-term attachment. This study uses a qualitative method with a literature study approach to analyze the effectiveness of content-based marketing in attracting Generation Z. The results show that an effective marketing strategy involves three main elements: the use of influencer marketing and user-generated content (UGC), content personalization with artificial intelligence (AI), and adaptation to algorithm changes and digital trends. By optimizing this strategy, brands can increase audience engagement, build trust, and drive customer loyalty. Therefore, a data-driven approach and creativity are key in ensuring the sustainability and competitiveness of digital marketing in the modern era.